Experimental Evidence for the Incorporation of Two Metals at Equivalent Lattice Positions in Mixed‐Metal Metal–Organic Frameworks. Issue 25 (11th March 2020) - Bitzer, Johannes; Otterbach, Steffen; Thangavel, Kavipriya; Kultaeva, Anastasia; Schmid, Rochus; Pöppl, Andreas; Kleist, Wolfgang
Abstract: Metal–organic frameworks containing multiple metals distributed over crystallographically equivalent framework positions (mixed‐metal MOFs) represent an interesting class of materials, since the close vicinity of isolated metal centers often gives rise to synergistic effects. However, appropriate characterization techniques for detailed investigations of these mixed‐metal metal–organic framework materials, particularly addressing the distribution of metals within the lattice, are rarely available. The synthesis of mixed‐metal FeCuBTC materials in direct syntheses proved to be difficult and only a thorough characterization using various techniques, like powder X‐ray diffraction, X‐ray absorption spectroscopy and electron paramagnetic resonance spectroscopy, unambiguously evidenced the formation of a mixed‐metal FeCuBTC material with HKUST‐1 structure, which contained bimetallic Fe−Cu paddlewheels as well as monometallic Cu−Cu and Fe−Fe units under optimized synthesis conditions. The in‐depth characterization showed that other synthetic procedures led to impurities, which contained the majority of the applied iron and were impossible or difficult to identify using solely standard characterization techniques. Therefore, this study shows the necessity to characterize mixed‐metal MOFs extensively to unambiguously prove the incorporation of both metals at the desired positions. The controlled positioning of metal centers in mixed‐metal metal–organic framework materials and the thorough characterization thereof is particularly important to derive structure–property or structure–activity correlations. Abstract : Two is company : The incorporation of Fe and Cu on crystallographically equivalent positions in a phase‐pure mixed‐metal HKUST‐1 material was proven using X‐ray absorption spectroscopy and electron paramagnetic resonance spectroscopy. In particular, this study showed that the presence of small amounts of other phases, which seemed neglectable based on standard characterization techniques, must not be ignored, since they might contain a major amount of one of the used metals.